1998
DOI: 10.1007/s004280050274
|View full text |Cite
|
Sign up to set email alerts
|

Changes in VEGF expression and in the vasculature during the growth of early-stage ethylnitrosourea-induced malignant astrocytomas in rats

Abstract: Vascular endothelial growth factor (VEGF), a potent angiogenic and vascular permeability factor, may be important as a mediator of brain tumour progression. However, it is still not clear whether VEGF plays a causative role in the early stage of glioma development. We investigated the relationship between VEGF protein expression (as assayed by immunohistochemistry) and different morphological parameters reflecting tumour progression (tumour diameter, vascular density and vascular diameter) in tumours at variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…ENU-induced glial tumors have been diagnosed as oligodendrogliomas (Vaquero et al 1994), astrocitomas (Yoshimura et al 1998), mixed gliomas, and ependimomas (Zook et al 2000). Histological and immunohistochemical data reported in the present work showed that oligodendrocytes were the major cellular lineage.…”
Section: Vegf Expressionmentioning
confidence: 64%
See 1 more Smart Citation
“…ENU-induced glial tumors have been diagnosed as oligodendrogliomas (Vaquero et al 1994), astrocitomas (Yoshimura et al 1998), mixed gliomas, and ependimomas (Zook et al 2000). Histological and immunohistochemical data reported in the present work showed that oligodendrocytes were the major cellular lineage.…”
Section: Vegf Expressionmentioning
confidence: 64%
“…Chemical induction of brain tumors by ethylnitrosourea has allowed the study of several aspects of neoplasm behavior, such as microvascular organization (Yoshimura et al 1998;Schlageter et al 1999), dedifferentiation (Jang et al 2004), gene mutations (O'Neill 2000Bielas and Heddle 2000), or experimental therapeutic agents (Kish et al 2001). However, aspects such as microcirculation and angiogenesis have scarcely been studied using this chemical model.…”
Section: Vegf Expressionmentioning
confidence: 99%
“…No significant increase (Wilcoxon log rank test, P = 0.18) in survival due to RP treatment was detected. tumors induced by ENU [48,49]. Increases in vascular permeability are thought to be associated with the angiogenic process and this is further supported by the size of the tumor (∼1-2 mm), which is within the range postulated for the development of vascular elements (the angiogenic switch [50][51][52]).…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the chemopreventative agents are gaining recognition as potentially having anti-angiogenic properties. As described above, VEGF has been shown to be expressed very early in the brain tumors induced by ENU [48,49]. All-trans retinoic acid (RA), 13-cis RA and all-trans retinol reduced VEGF secretion by human keratinocytes in primary cultures [57].…”
Section: Discussionmentioning
confidence: 99%
“…The causes of BBB breakdown in tumours are complex and partly related to the secretion of angiogenic stimulator molecules. Certainly, vascular endothelial growth factor (VEGF) has been implicated in the glial tumour angiogenesis (Yoshimura et al, 1998;Varlet et al, 2000;Chaudhry et al, 2001), but is also a potent vascular permeability factor Nagy et al, 1995). Angiogenesis in itself does not explain BBB breakdown because angiogenesis and increased vascular density are commonly observed with an intact BBB (e.g.…”
Section: Introductionmentioning
confidence: 96%